The role of rehabilitation in patients undergoing oesophagectomy for cancer and pre‐malignant disease: A qualitative exploration of the views of patients, carers and healthcare providers. (23rd January 2019) - Bull, Jeff; Oster, Candice; Flight, Ingrid; Wilson, Carlene; Koczwara, Bogda; Watson, David I.; Bright, Tim
Abstract: Objective: Oesophagectomy for cancer is associated with significant morbidity and mortality, and reduced quality of life. Structured rehabilitation potentially offers improved physical and psychological outcomes. We aimed to explore patient, carer and healthcare provider attitudes and preferences towards the role of rehabilitation. Methods: We interviewed 15 patients who had undergone an oesophagectomy, 10 carers and 13 healthcare providers about perceived impacts of treatment; preferred components of a rehabilitation program; barriers/enablers of support provision; and participation in rehabilitation programs. Data were analysed using framework analysis. Results: The overarching theme was "Getting back to normal." Diagnosis of disease signified a disruption to the normal trajectory of patients' lives and the post‐treatment period was characterised as striving to return to normal. Patients and carers focused on rehabilitation needs post‐treatment including dietary support, physiotherapy and healthcare provider support. Healthcare providers described rehabilitation as potentially beneficial from the pre‐treatment phase and, along with carers, highlighted the importance of psychological support. Barriers included access to services, cost of service provision and appointment burden. Conclusion: A need for rehabilitation services was identified by healthcare providers from the point of diagnosis, rather than only after surgery. Implications include improved service provision by healthcare institutions for patients undergoing oesophagectomy.